Effect of Screw Diameter in Femoral Fracture Fixation Modeled by Finite Element Method - Muhammad Nashrullah; Belladina Clara Shinta; Mas Irfan P. Hidayat; Agung Purniawan; Yuli Setiyorini (Institut Teknologi Sepuluh Nopember, 2017)
research in the field of biomechanics related to orthopedic implants is rapidly growing in the world, especially for fixation of fractured bone. Fixation is a surgery to locate and attach a plate pressed by screws at the fractured bone. Most of the fracture bones sited in femur. This research focuses on modeling and simulation of plate and screw made of SS316L material for the fixation of the fractured femur using finite element method (FEM). SS316L is a material with good biocompatibility, cheap, and ductile enough. Modeling and simulation done using ANSYS 15.0 software. Simulation results are stress, strain, and total deformation. It is obtained that optimum diameter of screw is 4.5 mm with respect to minimum value of von Mises stress and deformation.